Caracterização da logística reversa de pallets em indústrias de alimentos e bebidas no estado do Paraná - Maravieski, Vinicius Carvalho (2009)
The purpose of the study is to verify the process of Reverse Logistics of packaging in medium and large companies in the state of Paraná. The methodology used is classified as descriptive and exploratory, survey, with a quantitative - descriptive approach. The instrument used was a questionnaire with closed questions, which assessed the level of formalization of the flows of reverse logistics of packaging in the beverage and food industry. The sample consisted of thirty-nine industries, thirty of which are food companies and nine beverage companies. The qualitative analysis is to determine if the use of reverse logistics is an important factor in corporate strategy of logistics, the level of integration of reverse logistics flow with direct logistics flow and identify the level of formalization of the flow to the reverse logistics of reusable packaging. It was noticed that most companies view reverse logistics as an important factor for the corporate strategy of logistics, the reverse flows are integrated with direct logistics and the existence of different levels of formalization the flows of reverse logistics. The emphasis on the proactive use of reverse logistics by industries has provided the achievement of operational objectives of and competitive advantage.